2013
DOI: 10.1093/rheumatology/ket403
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon blockade in systemic lupus erythematosus: where do we stand?

Abstract: SLE is an autoimmune condition characterized by loss of tolerance to chromatin constituents and the production of ANAs. The majority of SLE patients display spontaneous expression of type I IFN-induced genes in circulating mononuclear cells and peripheral tissues, and type I IFNs play a role in the pathogenesis of the disease via the sustained activation of autoreactive T and B cells necessary for the production of pathogenic autoantibodies. Several IFN-blocking strategies are currently being evaluated in clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 54 publications
1
72
0
1
Order By: Relevance
“…80 Anti-IFNα therapy is under investigation in the "low" type I IFN subgroup of SLE patients, in whom it has been associated with clinical improvements. 81 Additional studies are needed to understand the function of type I IFNs in atherosclerosis and determine whether this class of cytokines is a therapeutic target.…”
Section: Induction Of Protective Treg Responsesmentioning
confidence: 99%
“…80 Anti-IFNα therapy is under investigation in the "low" type I IFN subgroup of SLE patients, in whom it has been associated with clinical improvements. 81 Additional studies are needed to understand the function of type I IFNs in atherosclerosis and determine whether this class of cytokines is a therapeutic target.…”
Section: Induction Of Protective Treg Responsesmentioning
confidence: 99%
“…2 These studies prompted the field to initiate investigations into the role of type I IFNs in SLE disease progression and associated comorbidities. The IFN signature clearly associates with disease in a large proportion of the patients and is nowadays considered an attractive target for therapeutic interventions.…”
Section: See Accompanying Article On Page 266mentioning
confidence: 99%
“…The IFN signature clearly associates with disease in a large proportion of the patients and is nowadays considered an attractive target for therapeutic interventions. 2 Several clinical trials targeting the type I IFN pathway have been initiated using either monoclonal antibody approaches or active immunization against IFN-α. A phase II trial using an antibody against the type I IFN receptor recently showed that it can accomplish suppression of the IFN profile and reduce disease activity in patients.…”
Section: See Accompanying Article On Page 266mentioning
confidence: 99%
“…Sifalimumab is a fully human immunoglobulin G1k monoclonal antibody that binds to and neutralizes a majority of the subtypes of human interferon-a. Phase I and Phase II trials in SLE patients have been performed with promising results including for cutaneous disease [82,83].…”
Section: Type I Interferon Blockadementioning
confidence: 99%